Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm working on the following problem:

Let $c\in(a,b)$ and $$f(x)=\begin{cases} 0 & a\leq x\leq c\\ 1 & c<x\leq b \end{cases}$$ $$\alpha (x)=\begin{cases} 0 & a\leq x< c\\ 1 & c\leq x\leq b \end{cases}$$

Show that $f\in R(\alpha)$

Unfortunately, what I seem to be proving is that $f\notin R(\alpha)$. My strategy was to show that given epsilon, we could find a partition $P_\epsilon $ such that the difference between the upper and lower sums is less than $\epsilon$.

So start by observing that for some $k$, $c\in[x_{k-1},x_k]$. Let $M_i=\sup_{x\in [x_{i-1},x_i]}f(x)$ and $m_i=\inf_{x\in [x_{i-1},x_i]}f(x)$. Fix $\epsilon>0$. Then

$$U\left(P,f,\alpha\right)-L\left(P,f,\alpha\right) = \sum_{i=1}^{N}\left(M_{i}-m_{i}\right)\left[\alpha\left(x_{i}\right)-\alpha\left(x_{i-1}\right)\right] = \sum_{i=1}^{k-1}\left(M_{i}-m_{i}\right)\left[\alpha\left(x_{i}\right)-\alpha\left(x_{i-1}\right)\right]+\left(M_{k}-m_{k}\right)\left[\alpha\left(x_{k}\right)-\alpha\left(x_{k-1}\right)\right]+\sum_{i=k+1}^{N}\left(M_{i}-m_{i}\right)\left[\alpha\left(x_{i}\right)-\alpha\left(x_{i-1}\right)\right] = (0-0)(0-0)+(1-0)(1-0)+(1-1)(1-1) = 1 $$

And as far as I know, 1 is not less than $\epsilon$ for many values of $\epsilon$. What am I doing wrong?

share|improve this question
    
shouldn't $\inf f(x) = 1$ in the interval $ c < x \le d $ –  Santosh Linkha Jan 16 '13 at 7:46
    
@experimentX yes I'll fix that. Thanks. –  crf Jan 16 '13 at 7:48

1 Answer 1

up vote 3 down vote accepted

In fact, you should want $c$ to be in your partition. So let $P = \{a = x_0 < x_1 < \ldots < x_k = c < \ldots < x_n = b\}$ be a partition. Then, letting $M_i = \sup_{x\in[x_{i-1}, x_i]} f(x)$ and $m_i = \inf_{x\in[x_{i-1},x_i]} f(x),$ we have:

$\begin{align*} U(P, f, \alpha) - L(P, f, \alpha) &= \sum_{i=1}^{n} (M_i - m_i)[\alpha(x_{i})-\alpha(x_{i-1})]\\ &= \sum_{i=1}^{k} (M_i - m_i)[\alpha(x_i) - \alpha(x_{i-1})] + \sum_{i=k+1}^{n} (M_i - m_i)[\alpha(x_i)-\alpha(x_{i-1})]\\ &= \sum_{i=1}^{k} (0-0)[\alpha(x_i)-\alpha(x_{i-1})] + \sum_{i=k+1}^{n} (M_i - m_i)[1-1]=0 < \epsilon \end{align*}$ for any $\epsilon.$ Hence, $f \in \mathscr{R}(\alpha).$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.